2020
DOI: 10.1109/access.2020.3004706
|View full text |Cite
|
Sign up to set email alerts
|

Deep Gaussian Process Regression for Performance Improvement of POS During GPS Outages

Abstract: Position and orientation system (POS) is a high-precision inertial navigation systems /Global navigation satellite system (INS/GNSS) integrated system that can continuously provide timespatial reference for airborne remote sensing, mobile mapping and vehicle localization using Kalman Filter (KF) during the availability of GPS measurements. However, the POS suffers from the GPS outages in some especial environment, whose accuracy of motion parameters degrades with the time accumulation. In order to suppress the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A BPNN [28] is a multilayer feedforward neural network in an artificial neural network, which is the most representative and extensive approach. The GPR [29], [34]- [36] is designed based on the Bayesian framework [37], [38] and is widely used in prediction tasks [39]- [41]. In SOH estimation, the inputs for the BPNNbased method, the GPR-based method, and the standard SVM-based method are also HF3 and HF4.…”
Section: Soh Estimation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A BPNN [28] is a multilayer feedforward neural network in an artificial neural network, which is the most representative and extensive approach. The GPR [29], [34]- [36] is designed based on the Bayesian framework [37], [38] and is widely used in prediction tasks [39]- [41]. In SOH estimation, the inputs for the BPNNbased method, the GPR-based method, and the standard SVM-based method are also HF3 and HF4.…”
Section: Soh Estimation Results and Discussionmentioning
confidence: 99%
“…where ( , ) is the kernel function. Due to its good ability to deal with nonlinear problems, the radial basis kernel is one of the most widely used functions [34]; it can be written as:…”
Section: { ∑( *mentioning
confidence: 99%
“…(2014) and Ye et al. (2018a, 2018b, 2020) suggested applying the Gaussian process regression (GPR) technique to cope with observation outages and restrain the INS error accumulation during GNSS signal failures. GPR has good applicability with strong generalisation capacity to resolve the high dimension, small sample size and nonlinear characteristic problems.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, SVM is of higher complexity arithmetic, and its kernel function selection and parameter adjustment has great influence on the prediction accuracy. Atia et al (2011 and Ye et al (2018aYe et al ( , 2018bYe et al ( , 2020 suggested applying the Gaussian process regression (GPR) technique to cope with observation outages and restrain the INS error accumulation during GNSS signal failures. GPR has good applicability with strong generalisation capacity to resolve the high dimension, small sample size and nonlinear characteristic problems.…”
Section: Introductionmentioning
confidence: 99%